2021
DOI: 10.1093/abbs/gmab097
|View full text |Cite
|
Sign up to set email alerts
|

Retardant effect of dihydroartemisinin on ulcerative colitis in a JAK2/STAT3-dependent manner

Abstract: Dihydroartemisinin (DHA) is a semi-synthetic derivative and the main active metabolite of artemisinin. The purpose of this study was to investigate the effect of DHA on the ulcerative colitis (UC) in both in vivo and in vitro models. Weight, survival rate, colon length, and Disease Activity Index score were used to evaluate the severity of colitis. Reverse transcription quantitative polymerase chain reaction and enzyme-linked immunosorbent assay were used to detect the expressions of cytokines interleukin (IL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The elevated expression and dysfunction of STAT3 lead to the persistence of synovial inflammation in RA patients and animal arthritis models. A previous study in ulcerative colitis revealed that DHA impeded inflammation by inhibiting the JAK/STAT pathway ( Jiang et al, 2021a ). Nonetheless, it was not clear whether DHA inhibited the JAK/STAT pathway in THP-1–derived macrophages and, consequently, reduced NLRP3 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated expression and dysfunction of STAT3 lead to the persistence of synovial inflammation in RA patients and animal arthritis models. A previous study in ulcerative colitis revealed that DHA impeded inflammation by inhibiting the JAK/STAT pathway ( Jiang et al, 2021a ). Nonetheless, it was not clear whether DHA inhibited the JAK/STAT pathway in THP-1–derived macrophages and, consequently, reduced NLRP3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, DC32, a DHA derivative, significantly suppressed the CIA via the Nrf2-p62-Keap1 feedback loop ( Fan et al, 2018a ) and inhibiting lymphocytic infiltration through downregulating the expression and transcription of IL-6 ( Fan et al, 2018b ). Another study in ulcerative colitis showed that DHA impeded inflammation by inhibiting the IL-6/signal transducer and activation of the transcription (STAT) 3 signaling pathway ( Jiang et al, 2021a ). STAT3 is one of the major signal transducers of JAKs and can be phosphorylated by JAK3.…”
Section: Introductionmentioning
confidence: 99%
“…Further exploration of the mechanism showed the anti-inflammatory effectiveness of dihydroartemisinin is connected to the blockage of the JAK2/STAT3 pathway. 85 Other signaling pathways including NF-κB and PI3K/AKT which play an important role in the of pathogenesis IBDs also shown to be mediated by dihydroartemisinin in DSS model. 86 Lei et al performed dihydroartemisinin treatment in the same rat model, and apart from the similar anti-inflammatory effect on cytokines, they also found that dihydroartemisinin can recover the abundance of the gut bacteria and the expression of cell junction-associated genes in UC.…”
Section: Dihydroartemisininmentioning
confidence: 99%
“…Taken together, the findings show that by promoting apoptosis of activated CD4 + T cells by HO-1 induction, dihydroartemisinin exerts its treating effect in the IBDs mouse model through regulating the Th/Treg Balance. 89 The Retardant effect of dihydroartemisinin on ulcerative colitis had been compared with dexamethasone 89 and 5-aminosalicylic acid, 85 both are clinical first-line drugs, 91 in which dihydroartemisinin was able to achieve a similar effect.…”
Section: Dihydroartemisininmentioning
confidence: 99%
“…Many inflammatory cytokines, such as members of the IL-1 family, play an important role in intestinal homeostasis and inflammation [ 8 ]. IL-18 has emerged as an indispensable factor in the regulation of host-microbial homeostasis and has been postulated to be a critical inducer for the development of UC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%